Child development - Santrock, John W. (Brown & Benchmark Publishers, 1994)
Now in its sixth edition, this text on child development contains increased and updated coverage of: culture, ethnicity and gender; families and parenting; and health and well-being. The research base has been updated and a strong socio-cultural emphasis is used throughout.